Examining Female Students’ Attitudes to English Oral Presentations. Do they Prefer to Speak Online or in Class? - Alzamil, Jwahir (International Journal of Language and Literary Studies, 2025)
Many learners of English as a second language find it difficult to speak in English. Delivering oral presentations in English is even more challenging. The goals of this study were to investigate: a) Saudi female university students’ attitudes towards English oral presentations in general; b) whether they face difficulties when delivering presentations online or in class; and c) whether they prefer to give presentations online or in class. The study was conducted with 128 Saudi female university-level students. The data instruments were an eighteen-item questionnaire and semi-structured interviews which examined three constructs: (a) their attitudes towards English oral presentations in general; (b) their attitudes towards online English oral presentations; and (c) their attitudes towards in-class English oral presentations. The results showed that: (a) the students had positive attitudes towards the importance of English oral presentations for the improvement of their language, even though such presentations make them nervous; (b) the students were less nervous while giving online presentations than they were while giving in-class presentations; (c) the students preferred online presentations to in-class presentations; and (d) the students preferred to deliver online presentations alone and in-class presentations as a part of a group.